Collision tumor of ovary: a rare combination of dysgerminoma and serous cystadenocarcinoma (Bangladesh Journal of Medical Science, 2014)
Collision tumors of ovary are rare neoplasms and most commonly consist of a teratoma with mucinous tumor. Combination of papillary serous cystadenocarcinoma and dysgerminoma was yet to be reported. A twenty years female patient presented with a large tumor of right ovary. Microscopically it was diagnosed as a collision tumor of ovary composed of dysgerminoma and serous cystadenocarcinoma. Mixed tumour can arise from divergent differentiation of a single type of stem cell. But components of collision tumor must arise from separate clones. Possibility of collision tumour should always kept in mind during assessment of difficult ovarian tumors to avoid diagnostic error. DOI: http://dx.doi.org/10.3329/bjms.v13i2.14955 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.224-227